MOLECULAR DETECTION AND DERMATO PATHOLOGICAL ANALYSIS OF ORF VIRUS INFECTION IN SHEEP AND GOATS IN BASRAH PROVINCE - Mohammed, Y. J.; Yousif, E. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was designed for the molecular diagnosis and assessment of histopathological changes of ORF infection in sheep and goats in Basra governorate in Iraq. The virus was detected by using -polymerase chain reaction. The samples were taken from the skin of the lips of animals infected with contiguous ecthema. Hundred samples taken from the sheep and 100 samples from goats of suspected animals, the results of the molecular diagnosis showed that 76 (76%) of sheep were infected and 71 (71%) of goats were infected by diagnosing the partial of ORFV037 gene (173bp), and ORFV039 (703bp), the sequences were determined and recorded in the NCBI and drawn the phylogenetic tree. The results of histopathological study showed presented various changes in cutaneous tissues in sheep include hyperplasia of hair follicles, sebaceous gland and sweet gland, parakeratosis, hyalinization of keratin Also to a picture of tumores, inflammation appear clearly in dermis also to hyperplasia of epidermis towered dermis. In goat showed prolifration of epidermis layer and papillae projection, Highly proliferation structures spinosum, sebaceous gland, sweet gland, and proliferation hair follicles with thickening it wall, hyperkeratosis of epidermis, infiltration of inflammatory cells and ulceration with necrotizing of epidermis.